Efficacy of Amflow®, a Real-Time-Portable Feedback Device for Delivering Appropriate Ventilation in Critically Ill Patients: A Randomised, Controlled, Cross-Over Simulation Study - Jong Won Kim; Sang O Park; Kyeong Ryong Lee; Dae Young Hong; Kwang Je Baek (Emergency Medicine International)
Objective. The aim of this study was to test whether Amflow® (a newly designed portable ventilation feedback device) can assist rescuers in delivering target tidal volume (VT) and respiration rate (RR) during self-inflating bag (SB) ventilations in various clinical scenarios. Method. This was a simulation study with a prospective cross-over design. A total of 40 trained participants who underwent training for SB ventilation were recruited. Using a SB with or without Amflow® alternately, participants delivered ventilations to test lungs connected to a gas flow analyser in each of three different scenarios: acute respiratory distress syndrome (ARDS; 315–385 ml ranges for 350 ml target VT, with 20 breaths/min); cardiopulmonary resuscitation (CPR; 450–550 ml ranges for 500 ml target VT with 10 breaths/min); and adult head trauma (630–770 ml ranges for 700 ml target VT with 15 breaths/min). Results. The feedback group (SB with Amflow®) demonstrated a significantly higher percentage of delivering the appropriate VT ranges than the no-feedback group for both ARDS (58.6% versus 23.5%, respectively) and CPR (85.4% versus 41.0%, respectively) (all p<0.05). However, there was no significant difference between the two groups in the percentage of delivering the appropriate VT ranges in head trauma patients (65.9% versus 68.3%, respectively; p=0.092). In all three scenarios, a higher percentage of target RR delivered was achieved in the feedback group (88.3%, 99.2%, and 96.3%, respectively) compared with the no-feedback group (5.8%, 12.5%, and 10.0%, respectively) (all p<0.05). Conclusion. The Amflow® device could be useful for rescuers in delivering SB ventilation with appropriate VT and RR simultaneously in various critical situations, except for clinical cases that demand greater delivered VT.